2016
DOI: 10.18325/jkmr.2016.26.3.153
|View full text |Cite
|
Sign up to set email alerts
|

A Rehabilitation for Total Hip Replacement in Korean Medicine: A Report of Three Cases

Abstract: The objective of this study was to propose a rehabilitation protocol for total hip replacement in Korean medicine and to report its effectiveness. Three patients who had undergone total hip replacement were treated using the rehabilitation protocol in Korean medicine. We evaluated the outcome evaluating physical examination findings of the hip joint, numeric rating scale, pain disability index, Harris hip score, and walking state. After the treatment, we observed that hip movement and muscular strength improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…A study found that the total hip replacement rehabilitation program enhanced hip motion and muscle strength, along with the patient's walking ability, Harris Hip Score, Pain Disability Index, and Numerical Pain Rating Scale [ 5 ]. According to Kariya et al, physiotherapy interventions, including quadriceps strengthening and bedside activity training, were effective in postoperative avascular necrosis for early restoration of strength, ROM, and functional activities [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study found that the total hip replacement rehabilitation program enhanced hip motion and muscle strength, along with the patient's walking ability, Harris Hip Score, Pain Disability Index, and Numerical Pain Rating Scale [ 5 ]. According to Kariya et al, physiotherapy interventions, including quadriceps strengthening and bedside activity training, were effective in postoperative avascular necrosis for early restoration of strength, ROM, and functional activities [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medical treatment for this condition is based on the Ficat and Arlet classification of the disease stage. In stages I and II, the joint surface is typically intact; therefore, conservative treatment with pharmacological therapy is indicated, but stages III and IV, which are more advanced, necessitate core decompression [ 4 ], osteotomy, and complete hip arthroplasty [ 1 , 5 ]. However, more recent therapeutic approaches have been created to administer stem cells to the necrotic areas to prevent fracture and collapse by repairing the femoral head's structural integrity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…보면 고관절 전치환술 7) , 슬관절 전치환술 8) , 골절 수술 9) 등 수술 후 한방 재활치료에 대한 연구, 척추 수술 후 증후군 환자에 대한 치험례 10) 및 연구 동향 11 Assessed by Wilcoxon signed rank test (median±range). NRS: numeric rating scale, EQ-5D-5L: five-level version of Euroqol-5 dimension, PDI: pain disability index, NDI: neck disability index, SPADI: shoulder pain and disability index, ODI: Oswestry disability index, LKSS: Lysholm knee score system, OKS: Oxford knee score.…”
Section: 근골격계 수술과 관련하여 시행된 선행 연구를 살펴unclassified
“…이 시기 동안 통증과 부기 관리, 수술 부위 보호, 관절 강직 방지 등을 목표로 한다 3,5,9,12) . 17,18) . 2단계부터는 기혈의 순환과 발목의 연부조직 회복을 위해 補益의 목적으로 十全大補湯 (甘草 4.0 g, 白茯苓 4.0 g, 白芍藥 4.0 g, 白朮 4.0 g, 熟地黃 4.0 g, 人蔘 4.0 g, 川芎 4.0 g, 黃芪 4.0g, 當歸 4.0 g, 肉桂 4.0 g/첩)을 사용하였다 19) .…”
Section: 서론»»»unclassified